Do Analysts and Auditors Use Information in Accruals? - Bradshaw, Mark T.; Richardson, Scott A.; Sloan, Richard G. (Journal of Accounting Research, 2001)
Existing research indicates that firms with high accruals are more likely to experience future earnings problems, but that investors' expectations, as reflected in stock prices, do not appear to anticipate these problems. In this paper, we directly examine the published opinions of two types of professional investor intermediaries to see if they provide investors with information concerning the future earnings problems experienced by firms with high accruals. First, we examine the earnings forecasts of sell‐side analysts. We show that analysts' earnings forecasts do not incorporate the predictable future earnings declines associated with high accruals. Second, we examine the behavior of independent auditors. We find no evidence that auditors signal the future earnings problems associated with high accruals through either their audit opinions or through auditor changes. Overall, our evidence indicates that analysts and auditors do not alert investors to the future earnings problems associated with high accruals, thus corroborating previous findings that investors do not appear to anticipate these problems.